Cigarette whole smoke solutions disturb mucin homeostasis in a human in vitro airway tissue model. (1st November 2018) - Cao, Xuefei; Wang, Yiying; Xiong, Rui; Muskhelishvili, Levan; Davis, Kelly; Richter, Patricia A.; Heflich, Robert H.
Abstract: Many cigarette smoke-associated airway diseases involve alterations in mucin homeostasis. With the rationale that relevant tissue responses can be measured to evaluate the adverse health effects of tobacco products, we assessed changes in mucin secretion and the density and size of goblet cells in an in vitro human air-liquid-interface (ALI) airway tissue model after exposure to a tobacco smoke solution. Cultures were exposed daily for up to five consecutive days to a whole smoke solution (WSS) prepared by machine smoking Marlboro Red or Marlboro Silver cigarettes using the Canadian Intense (CI) protocol. Both WSSs induced concentration- and time-related hypersecretion of mucins 5AC and 5B, accompanied by up-regulation of the respective mucin genes. Mucin secretion returned to baseline levels following a 14-day recovery period. Mucin-secreting goblet cells exhibited increased cell density and decreased size after 5 daily treatments then recovered to their normal size, but with decreased cell density, 14 days after the last treatment. The beating frequency of ciliated cells, which plays a key role in mucociliary clearance, was increased by 5 daily treatments with the CI WSSs then reverted to baseline levels following a 7-day recovery. Taken together, our results indicate that ALI cultures can be used to measure the modulation of mucin production, secretion, and clearance, disturbances that are manifested in tobacco smoke-related diseases, such as chronic obstructive pulmonary disease. Measuring tissue responses directly relevant to the respiratory toxicity of cigarette smoke may provide useful information in support of science-based regulatory decisions.